2020
DOI: 10.3390/en13051033
|View full text |Cite
|
Sign up to set email alerts
|

An Image Processing-Based Method to Assess the Monthly Energetic Complementarity of Solar and Wind Energy in Colombia

Abstract: Solar and wind energy systems, without storage, cannot satisfy variable load demands, but their combined use can help to solve the problem of the balance between generation and consumption. Energetic complementarity studies are useful to evaluate the viability of the use of two or more renewable energy sources with high variability in a specific interval of time in a determined region. In this paper, the monthly energetic complementarity study of solar and wind resources of Colombia is carried out. A novel app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…According to the Mining and Energy Planning Unit (UPME), Colombia has an average monthly solar irradiance that varies between 4.0 and 6.0 kWh/m 2 /day (Muñoz et al, 2014;Peña-Gallardo et al, 2020); being the departments of the Caribbean Region where the highest average irradiance values are presented, between 5.2 to 6.8 kWh/m 2 , which exceeds the world average value of 3.9 kWh/m 2 (Chamorro et al, 2017). This region has between 5.0 and 6.5 sun hours daily on average (Ramírez-Cerpa et al, 2017).…”
Section: Solar Energy Potential Of the Colombian Caribbean Regionmentioning
confidence: 99%
“…According to the Mining and Energy Planning Unit (UPME), Colombia has an average monthly solar irradiance that varies between 4.0 and 6.0 kWh/m 2 /day (Muñoz et al, 2014;Peña-Gallardo et al, 2020); being the departments of the Caribbean Region where the highest average irradiance values are presented, between 5.2 to 6.8 kWh/m 2 , which exceeds the world average value of 3.9 kWh/m 2 (Chamorro et al, 2017). This region has between 5.0 and 6.5 sun hours daily on average (Ramírez-Cerpa et al, 2017).…”
Section: Solar Energy Potential Of the Colombian Caribbean Regionmentioning
confidence: 99%
“…For the implementation of hybrid systems, it is necessary to consider technical aspects such as the load, meteorological variations and geographical location, which defines the energy potential that can be used (Lian et al, 2019). The implementation of these systems allows improving the quality of life in rural areas, through the promotion of sustainable development policies, energy efficiency programs and the possibility of attracting foreign investment for national projects (Gallardo et al, 2020;Castro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the complementarity between wind and solar energy has been investigated in China [2,7,8], United States [9,10], Colombia [3,11], Australia [12], Mexico [5], Lesotho [13], Germany [1], Algeria [14], Poland [15], and France [16]. Numerous related publications have also been comprehensively discussed in the review studies by [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, the authors reported that wind-solar complementarity in hybrid systems is superior to that between wind or solar energy plants in different regions. [11] applied a novel approach based on image processing to conduct a monthly energetic complementarity study of wind and solar energy resources in Colombia. The results, which have translated into energetic complementarity maps, indicate that projects involving the combined use of wind and solar systems could be developed in the northern and northeastern regions of the country.…”
Section: Introductionmentioning
confidence: 99%